Investigations into light-matter interaction in photonic random media for imaging applications - Gayathri Radhakrishnan (Nanyang Technological University, 2022)
A photonic random medium is one in which, light scatterers are distributed in a spatially random fashion and light entering such a medium experiences multiple scattering events. The resulting ‘random walk’ like propagation of light increases its path length, leading to more and more interactions with the medium and has the potential to alter the nature of optical processes involved. Photonic random media thus provide platforms for enhanced light-matter interaction, and in the presence of an appropriate gain medium, it is possible to obtain coherence-tunable, quasi-monochromatic lasing emission called random lasing. This thesis explores ways to enhance such interactions, thereby ensuring efficient random lasing and to employ them in real-world applications such as wide-field and diagnostic imaging. The first part of the thesis focuses on enhancing the scatterer performance for developing a low threshold plasmonic random laser. The interaction of light with anisotropic plasmonic structures such as nano-urchins and nanorods is analysed for this purpose and optimised using simulation methods. With tailored spectral overlap and optimised aspect ratio, it was possible to achieve random lasing emission at an extremely low threshold of 116 µJ/cm2. A wide-field imaging microscope developed using this plasmonic random laser produces high-contrast images with sub-micron resolution, devoid of coherent artefacts. A quantitative comparison of fluorescence images shows that the random laser could outperform both conventional lasers and LEDs as they combine the laser-like properties with spatial incoherence. The dependence of random lasing signals on the variations on the surface of the scattering substrate is investigated in the second part. Polymer random lasers with wrinkle-like microstructures of different surface roughness values are fabricated using a bio-inspired approach in this study. The observation that random lasing parameters are highly reliant on substrate roughness motivates the development of a diagnostic system based on this dependence. The roughness of tissues varies during the progression of tumour. Hence, the random lasing signals emerging from the tissues provide spectral information on tumour growth, while simultaneously functioning as an imaging source. Thus, a bi-modal spectroscopic and imaging system is devised, allowing for the early diagnosis of tumour growth.